Predicting Anxiety in Routine Palliative Care Using Bayesian-Inspired Association Rule Mining - Haas, Oliver; Lopera Gonzalez, Luis Ignacio; Hofmann, Sonja; Ostgathe, Christoph; Maier, Andreas; Rothgang, Eva; Amft, Oliver; Steigleder, Tobias (Frontiers in Digital Health, 2021)
We propose a novel knowledge extraction method based on Bayesian-inspired association rule mining to classify anxiety in heterogeneous, routinely collected data from 9,924 palliative patients. The method extracts association rules mined using lift and local support as selection criteria. The extracted rules are used to assess the maximum evidence supporting and rejecting anxiety for each patient in the test set. We evaluated the predictive accuracy by calculating the area under the receiver operating characteristic curve (AUC). The evaluation produced an AUC of 0.89 and a set of 55 atomic rules with one item in the premise and the conclusion, respectively. The selected rules include variables like pain, nausea, and various medications. Our method outperforms the previous state of the art (AUC = 0.72). We analyzed the relevance and novelty of the mined rules. Palliative experts were asked about the correlation between variables in the data set and anxiety. By comparing expert answers with the retrieved rules, we grouped rules into expected and unexpected ones and found several rules for which experts' opinions and the data-backed rules differ, most notably with the patients' sex. The proposed method offers a novel way to predict anxiety in palliative settings using routinely collected data with an explainable and effective model based on Bayesian-inspired association rule mining. The extracted rules give further insight into potential knowledge gaps in the palliative care field.
Keywords: anxiety; machine learning; association rule mining; palliative care; routine data; questionnaire

SOP - Handling of multidrug-resistant Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Hans Bernd; Foertsch, Baerbel; Klein, Carsten (Onkologe, 2018)
EVALuna2:36423

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

SOP – Umgang mit multiresistenten Erregern auf der Palliativstation - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Förtsch, Bärbel; Klein, Carsten (Onkologe, 2017)
CRIS-Team Scopus Importer:2024-02-26

The palliative care team in the intensive care unit - Ostgathe, Christoph; Klein, Carsten; Heckel, Maria; Hofmann, Sonja; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2012)
The aim of palliative care is to relieve suffering and stabilize or improve quality of life. Prolongation of life and focus on quality of life seem to be at first glance mutually exclusive. However, in daily clinical routine they occasionally do simultaneously occur, when further medical treatment to prolong life is not successful, not appropriate, or simply refused by the patient. In general, basic competencies in palliative care should be offered by the intensive care unit teams. In complex cases, it can be reasonable to integrate a palliative care team (PCT) which can support treatment for those patients with regard to symptom-oriented therapy. They also facilitate referral of seriously ill patients to a hospice or home. Palliative care consultation is recommended, if distressing symptoms can not be alleviated sufficiently or support for referral of terminally ill patients is sought. In addition, a PCT can provide support in discussions about withdrawal of life-prolonging treatments and the aims of therapy. © 2012 Springer-Verlag.
Keywords: Communication; Palliative care; Palliative care team; Quality of life; Therapy